SUPPORT SYSTEM FOR MANAGEMENT OF GREEN SPACES IN PERMANENT PRESERVATION OF URBAN WATER BODIES - Bressane, Adriano [UNESP]; Mochizuki, Patricia Satie; Frutuoso Roveda, Jose Arnaldo [UNESP]; Batista Salvador, Nemesio Neves (Centro Pesquisas Florestais, Ufsm, 2016)
The conservation of urban green areas is among the key strategies for achieving healthy and sustainable cities. However, the multiplicity of the involved factors requires an integrated analysis by means of a logical and structured procedure. Therefore, this article aims to present the proposal for a decision support system for the management of green areas in public domain, in areas of permanent preservation of urban water bodies. For its development, guidelines of the plannning method through scenarios were adopted, by which the aspects related to the problem and routing solutions were analysed. The main used materials correspond to the works of technical literature and legislation, raised through search terms along with bibliographic and legislative seats. From the analysis of these materials, we studied the actual functions of these areas of permanent preservation and the factors affecting their performance and protection. As a result, we obtained a structured model in key decision for the selection of the location alternatives and their function-space capability.
Keywords: decision support; permanent preservation area; green area of public domain